Editorial note - Jovan Shopovski (European Scientific Journal, ESJ, 2014)
Dear Researcher, We are proud to announce to you that in the past 3.5 years, over 7,000 scientists from all around the globe have published their academic attainments with the European Scientific Journal, ESJ. This journal website has reached over 100,000 unique visitors per month and hard copies of researchers published works have been disseminated globally by the ESJ. Despite raising the operation costs, we have been able to maintain a specific amount of publication fee over the years. From the very inception of its internationalization, the ESJ has promoted agile review procedure ruling out the unacceptable practice imposed, where researchers spend years waiting for submission`s feedback. In this regard, special gratitude goes to our editorial board members for their efforts, hard work and academic professionalism. Also, academicians from over 150 different Universities and Centers are currently part of the ESJ`s editorial team, and they have successfully contributed to the promotion of our mission - to provide greater and faster flow of the newest scientific thoughts. Every month, three issues of the ESJ are uploaded on our website, embracing different academic disciplines and facilitating the cutting edge concepts of interdisciplinarity, multidisciplinarity and transdisciplinarity. They are: • Issue 1: Economics, Law and Education • Issue 2: Humanities • Issue 3: Life Sciences Finally, the gold open access concept is strictly promoted along with our publication activities. Therefore, researchers, practitioners and visitors are able to access and download the full ESJ`s content without charges. Fully aware of the restrictions that subscription policies have imposed, we are devoted to establishing open access standards, making our content freely available to those who need it the most - the academicians. In spite of some occasional barriers and obstructions from those who still believe that science is only for those who can afford paying huge amounts for access, we will persistently continue our global activities of publishing quality papers regardless of authors` geographical origin, gender, academic title, age, race or religion. Hence, the thousands of submissions by authors and researchers from six continents is an acknowledgement of our role and influence in the modern publishing processes. Thank you for your quality recognition. Indeed, you are motivating and nurturing the prominence of our work. Sincerely, Jovan Shopovski July 2014 European Scientific Journal, ESJ -Editor in Chiefhttp:// eujournal.org/index.php/esj